Preparation and Catalytic Properties of Iron-Cerium Phosphates with Sodium Dodecyl Sulfate. (26th December 2012) - Onoda, Hiroaki; Sakumura, Takeshi
Abstract : Iron phosphate was prepared from iron nitrate and phosphoric acid with sodium dodecyl sulfate at various stirring hours. The chemical composition of the obtained samples was estimated from ICP and XRD measurements. Particle shape and size distribution were observed by SEM images and laser diffraction/scattering methods. Further, the catalytic activity was studied with the decomposition of the complex between formaldehyde, ammonium acetate, and acetylacetone. The peaks of FePO4 were observed in XRD patterns of samples prepared in Fe/Ce = 10/0 and then heated at 600°C. Other samples were amorphous in XRD patterns. Iron-cerium phosphates had high catalytic activity for the decomposition of the complex.